Real-world antidiabetic drug use and fracture risk in 12,277 patients with type 2 diabetes mellitus: a nested case–control study - Losada, E; Soldevila, B; Ali, M; Martínez-Laguna, D; Nogués, X; Puig-Domingo, M; Díez-Pérez, A; Mauricio, D; Prieto-Alhambra, D (Springer, 2018)
Summary We conducted a nested case–control study to study the association between antidiabetic treatments (alone or in combination) use and fracture risk among incident type 2 Diabetes mellitus patients. We found an increased risk of bone fracture with insulin therapy compared to metformin monotherapy. Introduction Patients with type 2 diabetes mellitus (T2DM) have an increased risk of fragility fractures, to which antidiabetic therapies may contribute. We aimed to characterize the risk of fracture associated with different antidiabetic treatments as usually prescribed to T2DM patients in actual practice conditions. Methods A case–control study was nested within a cohort of incident T2DM patients registered in 2006–2012 in the Information System for Research Development in Primary Care (Catalan acronym, SIDIAP), a database which includes records for > 5.5 million patients in Catalonia (Spain). Each case (incident major osteoporotic fracture) was risk-set matched with up to five same-sex controls by calendar year of T2DM diagnosis and year of birth (± 10 years). Study exposure included previous use of all antidiabetic medications (alone or in combination), as dispensed in the 6 months before the index date, with metformin (MTF) monotherapy, the most commonly used drug, as a reference group (active comparator). Results Data on 12,277 T2DM patients (2049 cases and 10,228 controls) were analyzed. Insulin use was associated with increased fracture risk (adjusted OR 1.63 (95% CI 1.30–2.04)), as was the combination of MTF and sulfonylurea (SU) (adjusted OR 1.29 (1.07–1.56)), compared with MTF monotherapy. Sensitivity analyses suggest possible causality for insulin therapy but not for the MTF + SU combination association. No significant association was found with any other antidiabetic medications. Conclusions Insulin monotherapy was associated with an increased fracture risk compared to MTF monotherapy in T2DM patients. Fracture risk should be taken into account when starting a glucose-lowering drug as part of T2DM treatment.